Super-large record-breaking mitochondrial genome of Cathaya argyrophylla in Pinaceae - Huang, Kerui; Xu, Wenbo; Hu, Haoliang; Jiang, Xiaolong; Sun, Lei; Zhao, Wenyan; Long, Binbin; Fan, Shaogang; Zhou, Zhibo; Mo, Ping; Jiang, Xiaocheng; Tian, Jianhong; et al. (Frontiers in Plant Science, 2025)
IntroductionMitochondrial genomes (mitogenomes) in Pinaceae are notable for their large size and complexity. This study investigates the mitogenome of the critically endangered Cathaya argyrophylla to understand the drivers of its exceptional genome expansion.MethodsWe sequenced, assembled, and annotated the C. argyrophylla mitogenome. Comparative analyses were performed against other Pinaceae species and gymnosperms, examining repeat sequences, transposable elements (LINEs, LTRs), RNA editing events, chloroplast-derived sequence transfers (mtpts), and nuclear genome homology.ResultsThe C. argyrophylla mitogenome is a record-breaking 18.99 Mb. While C. argyrophylla and other extremely large Pinaceae mitogenomes possess substantial repeats and elevated transposon activity, these factors alone do not explain their size. Significant incorporation of mtpts was observed. Additionally, large mitogenomes exhibited distinct RNA editing patterns and reduced nuclear homology compared to smaller genomes.DiscussionMassive Pinaceae mitogenomes are characterized by a combination of features: substantial repeat content, elevated transposon activity, extensive plastid sequence integration, and distinct RNA editing and nuclear homology patterns. This comprehensive analysis enhances our understanding of plant mitogenome evolution and provides a genomic foundation for C. argyrophylla conservation and potential applications.